Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Villas Bôas, Ana B.; Ardhuin, Fabrice; Ayet, Alex; Bourassa, Mark A.; Brandt, Peter; Chapron, Betrand; Cornuelle, Bruce D.; Farrar, J. T.; Fewings, Melanie R.; Fox-Kemper, Baylor; Gille, Sarah T.; Gommenginger, Christine; et al. (Frontiers in Marine Science, 2019)
Ocean surface winds, currents, and waves play a crucial role in exchanges of momentum, energy, heat, freshwater, gases, and other tracers between the ocean, atmosphere, and ice. Despite surface waves being strongly coupled to the upper ocean circulation and the overlying atmosphere, efforts to improve ocean, atmospheric, and wave observations and models have evolved somewhat independently. From an observational point of view, community efforts to bridge this gap have led to proposals for satellite Doppler oceanography mission concepts, which could provide unprecedented measurements of absolute surface velocity and directional wave spectrum at global scales. This paper reviews the present state of observations of surface winds, currents, and waves, and it outlines observational gaps that limit our current understanding of coupled processes that happen at the air-sea-ice interface. A significant challenge for the coming decade of wind, current, and wave observations will come in combining and interpreting measurements from (a) wave-buoys and high-frequency radars in coastal regions, (b) surface drifters and wave-enabled drifters in the open-ocean, marginal ice zones, and wave-current interaction ``hot-spots'', and (c) simultaneous measurements of absolute surface currents, ocean surface wind vector, and directional wave spectrum from Doppler satellite sensors.